Systematic Literature Review : Pemberdayaan Masyarakat Inklusif Untuk Mewujudkan Keadilan Sosial - Sholichah, Hidayatus; Al Fajar, Adam Hafidz; Syamraeni, Syamraeni; Mudfainna, Mudfainna (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
The urgency of this research arises from the need for more inclusive community empowerment as a measure to address growing social inequality. This research aims to explore empowerment approaches that involve all levels of society, including vulnerable groups, in order to create sustainable social justice. The research method used is Systematic Literature Review (SLR), which includes analysing the literature on inclusive empowerment, social inclusion, and its impact on education and health. Data was collected from various relevant academic sources, published between 2019 and 2023, to ensure relevance to the latest trends in social development. The results show that inclusive community empowerment strengthens access to education and health for all, especially marginalised groups. In education, inclusive approaches increase participation and individual potential, leading to reduced social and economic inequality. In health, better access for vulnerable groups, such as people with disabilities and the poor, ensures equitable distribution of health services through disability-friendly facilities and digital services such as e-counselling for stunting. In conclusion, inclusive empowerment plays a crucial role in realising social justice and creating a more resilient, inclusive and competitive society.